2015
DOI: 10.1007/s00284-015-0890-y
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Unsaturated Fatty Acids (Low Melting Point) of Broiler Fatty Waste Obtained Through Staphylococcus xylosus Fermentation

Abstract: The increasing rise in the production of meat around the world causes a significant generation of agro-industrial waste--most of it with a low value added. Fatty wastes have the potential of being converted into biodiesel, given the overcome of technological and economical barriers, as well as its presentation in solid form. Therefore, the aim of this work was to investigate the capacity of Staphylococcus xylosus strains to modify the chemical structure of chicken fatty wastes intending to reduce the melting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In this process, the heat induces the aggregation of the proteins into filaments or densely branched clusters which interact as “sticky” molecules (Hsien and Regenstein, 1992). Moreover, between 44 ℃ and 65 ℃, there is a phase change from solid to liquid of the fats (melting) present in the egg yolk powder (Marques et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, the heat induces the aggregation of the proteins into filaments or densely branched clusters which interact as “sticky” molecules (Hsien and Regenstein, 1992). Moreover, between 44 ℃ and 65 ℃, there is a phase change from solid to liquid of the fats (melting) present in the egg yolk powder (Marques et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In this process, the heat induces the Food Science and Technology International 27(2) aggregation of the proteins into filaments or densely branched clusters which interact as ''sticky'' molecules (Hsien and Regenstein, 1992). Moreover, between 44 C and 65 C, there is a phase change from solid to liquid of the fats (melting) present in the egg yolk powder (Marques et al, 2015). All these processes involve a series of physical and chemical changes that affect the a w values of the egg powders.…”
Section: Changes In Egg Powder's Water Activity With Temperaturementioning
confidence: 99%
“…We found that after reaching the lowest estimated melting point, the fat waste then exhibited an increase in melting point as both fermentation time and fat concentration increased; similar process characteristics have been previously reported. 42 …”
Section: Discussionmentioning
confidence: 99%